Delayed policy responses to COVID-19: The role of the WHO's structural problem - Mira Fischer (WZB Berlin Social Science Center, 2020)
In the current coronavirus pandemic, the WHO must gather facts and formulate policy recommendations. However, the interlacing of both tasks within one organization is problematic.
Keywords: 300; contagious disease; Coronavirus; COVID-19; epidemic; health policy; institutional factors; international politics; WHO